Trease and Evans pharmacognosy - Evans, William Charles; Evans, Daphne; Trease, George Edward, 1902-1986 (Edinburgh ; New York : Saunders/Elsevier, 2009)
Since the previous edition was published in 2002 there have been notable developments in many areas covering the whole field of pharmacognosy. This edition has been updated to include these changes
Plants in medicine : the origins of pharmacognosy -- The scope and practice of pharmacognosy -- Plant nomenclature and taxonomy -- Biological and geographical sources of drugs -- A taxonomic approach to the study of medicinal plants and animal-derived drugs -- Pharmacological activities of natural products -- Synergy and other interactions in phytomedicines / E.M. Williamson -- Traditional plant medicines as a source of new drugs / P.J. Houghton -- Discovering new lead compounds in pharmaceutical research and development / M.J. O'Neill and J.A. Lewis -- Commerce in crude drugs / R. Baker -- Production of crude drugs -- Plant growth regulators -- Plant cell and tissue culture : biochemical conversions ; clonal propagation -- Phytochemical variation within a species -- Deterioration of stored drugs -- Quality control -- General methods associated with the phytochemical investigation of herbal products -- Basic metabolic pathways and the origin of secondary metabolites -- Hydrocarbons and derivatives -- Carbohydrates -- Phenols and phenolic glycosides -- Volatile oils and resins -- Saponins, cardioactive drugs and other steroids -- Miscellaneous isoprenoids -- Cyanogenetic glycosides, gluosinolate compounds, cysteine derivatives and miscellaneous glycosides -- Alkaloids -- The search for naturally derived anticancer agents -- Antiprotozoal natural products / C.W. Wright -- An overview of drugs with antihepatotoxic and oral hypoglycaemic activities -- Antibacterial and antiviral drugs -- Vitamins and hormones -- The plant nutraceuticals / G.B. Lockwood -- Colouring and flavouring agents -- Miscellaneous products -- Herbal medicine in Britain and Europe : regulation and practice / S.Y. Mills -- Asian medicine / S.E. Weston -- Chinese herbs in the West / S.Y. Mills -- Plants in African traditional medicine--some perspectives / A. Sofowora -- Hallucinogenic, allergenic, teratogenic and other toxic plants -- Pesticides of natural origin -- Plant description, morphology and anatomy -- Cell differentiation and ergastic cell contents -- Techniques in microscopy
Includes bibliographical references and index
Keywords: Pharmacognosy; Pharmacognosy